FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINGKAT KEMANDIRIAN PETANI KEDELAI DI KECAMATAN JATIWARAS KABUPATEN TASIKMALAYA - Ivan Sayid Nurahman; Tiktiek Kurniawati (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The development of domestic soybean production which tends to be slow causes the demand for soybeans to be unable to be fulfilled every year even though various government programs have been rolled out. The inability of local soybeans to meet domestic demand for soybeans causes dependence on imported soybeans. The use of good and appropriate farmer empowerment methods becomes an urgency, so that farmers become empowered and have independence. This study aims to determine the level of independence of soybean farmers and analyze the factors that affect the level of independence of farmers in Jatiwaras District, Tasikmalaya Regency. The research will be carried out using a survey method in Jatiwaras District, Tasikmalaya Regency which is a potential soybean development area in West Java by taking a sample of 127 soybean farmers using simple random sampling. The data collected in this study consisted of secondary data and primary data. The data analysis method used in this research is descriptive analysis and multiple linear regression analysis. The results showed that (1) the level of independence of soybean farmers in Jatiwaras District was in the moderate category, (2) motivation, ability, socio-cultural environment, extension performance, empowerment, and participation had a significant effect on the independence of soybean farmers, while dynamism had no significant effect.